Pools and Cross-Licensing in the Shadow of Patent Litigation - Jay Pil Choi (Center for Economic Studies and ifo Institute (CESifo), 2003)
Most patent pools are formed in the shadow of patent litigation as an attempt to settle disputes in regard to conflicting infringement claims and the validity of patents. To reflect this reality, I develop a simple framework to analyze the incentives to form a patent pool or engage in cross-licensing arrangements in the presence of uncertainty as to the validity and coverage of patents that makes disputes inevitable. I analyze private incentives to litigate and compare them with the social incentives. Antitrust implications of patent pools are considered. The effects of patent pools on third party incentives to challenge the validity of patents and on development incentives are also investigated.
Keywords: 330; patent pools; cross-licensing; complements and substitutes; patent litigation